2013
DOI: 10.4161/rna.24682
|View full text |Cite
|
Sign up to set email alerts
|

Conformational readout of RNA by small ligands

Abstract: RNA molecules have highly versatile structures that can fold into myriad conformations, providing many potential pockets for binding small molecules. The increasing number of available RNA structures, in complex with proteins, small ligands and in free form, enables the design of new therapeutically useful RNA-binding ligands. Here we studied RNA ligand complexes from 10 RNA groups extracted from the protein data bank (PDB), including adaptive and non-adaptive complexes. We analyzed the chemical, physical, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
7
13
0
Order By: Relevance
“…Further we extracted the RNA interfaces and compared the structural features of the RNA to the features extracted from a data set of all RNA interfaces of the RNA-binding domains. Consistent with the knowledge that most RBPs bind ssRNA 33,42,43 we observed an overall preference for non-paired nucleotides in the RNA interfaces bound to the proteins, except for interfaces extracted from proteins belonging to the dsRBD family, which expectedly were enriched with the standard Watson-Crick pairing (WWcis). While for most RBPs we did not noticed any preference for a unique RNA-conformation at the RNA-protein interfaces, in some domain families, specifically in the RRM, we observed a significant enrichment for the rare RNA conformations, C2' endo and syn at the binding interface ( Table 1).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Further we extracted the RNA interfaces and compared the structural features of the RNA to the features extracted from a data set of all RNA interfaces of the RNA-binding domains. Consistent with the knowledge that most RBPs bind ssRNA 33,42,43 we observed an overall preference for non-paired nucleotides in the RNA interfaces bound to the proteins, except for interfaces extracted from proteins belonging to the dsRBD family, which expectedly were enriched with the standard Watson-Crick pairing (WWcis). While for most RBPs we did not noticed any preference for a unique RNA-conformation at the RNA-protein interfaces, in some domain families, specifically in the RRM, we observed a significant enrichment for the rare RNA conformations, C2' endo and syn at the binding interface ( Table 1).…”
Section: Resultssupporting
confidence: 88%
“…32 Further, we demonstrated that nucleotides possessing the rare conformations are preferentially involved in direct interactions between RNA and small ligand. 33 Here we show that rare RNA conformations are also prevalent among nucleotides which bind proteins, specifically via the RRM domain. This suggests that RNA conformation may contribute to the recognition code by which proteins can specifically identify their targets.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…These interactions fine-tune the specificity of RNA interactions by determining structure at the 3D level [22]. Interestingly, non-canonical pairs were also found to be involved in ligand binding sites [8,19], which corroborates with further findings showing that some secondary structure motifs can specify ligand binding [6,48].…”
Section: Rna Structuresupporting
confidence: 75%
“…Such structures can be as intricate and stable as those formed by proteins and can recognize small-molecule ligands, other nucleic acids, and/or proteins with high affinity and specificity. [21][22][23][24] At the same time, the highly dynamic conformation and repetitive character of its surface presents difficulties for drug design. 25,26 In addition, many putative small molecule-binding pockets in RNA are much more polar and solvent exposed than binding sites on proteins, complicating ligand design efforts.…”
mentioning
confidence: 99%